A polyamide separation composite membrane post-treatment method

CN122974147APending Publication Date: 2026-10-27TAIZHOU HEYI NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611485437.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]针对现有技术中聚酰胺分离复合膜后处理方法无法兼顾高水通量、高截留率以及涂层易脱落导致抗污染性能衰减的技术问题,本发明提供了一种聚酰胺分离复合膜后处理方法及其制备得到的聚酰胺分离复合膜

Benefits of technology

其一,本发明突破了水通量与脱盐率的传统博弈效应。通过前期柠檬酸温和扩孔结合后期络合物靶向精准修复大孔缺陷,制备得到的复合膜在保持甚至略微提升原有高截留率的前提下,纯水通量实现了成倍的增长,有效提升了膜分离效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974147A_ABST
    Figure CN122974147A_ABST
Patent Text Reader

Abstract

The application discloses a kind of polyamide separation composite membrane post-processing method, belong to membrane separation technical field.The method includes: the nascent polyamide composite membrane is immersed in the first post-processing liquid including citric acid, glycerol and deionized water and is carried out swelling treatment;Membrane surface residual liquid is removed using physical method;After liquid removal, the composite membrane is immersed in the second post-processing liquid including tannin acid, single-end amino polyether, antioxidant and deionized water and is carried out modification treatment;Finally, wash and dry.The application is by the mild swelling and pore preserving effect of citric acid and glycerol to unmask the internal reaction group of polyamide network, then in situ targeted anchoring and repair is carried out using the complex formed by tannin acid and single-end amino polyether.The method effectively breaks the game effect of composite membrane water flux and rejection rate, greatly improves water flux while maintaining very high desalination rate, endows the membrane surface with excellent long-term anti-pollution performance, and the process flow is easy to implement industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membrane separation technology, and in particular to a post-processing method for a polyamide separation composite membrane. Background Technology

[0002] Polyamide composite membranes are widely used in reverse osmosis and nanofiltration water treatment. Their separation performance mainly relies on the dense polyamide separation layer formed by interfacial polymerization. However, there is an intrinsic trade-off between the water permeability and solute rejection rate of the separation membrane, which greatly limits further improvement in membrane separation efficiency. To overcome this trade-off and endow composite membranes with fouling resistance, researchers have developed various membrane post-treatment technologies to increase water flux without sacrificing rejection rate.

[0003] The most traditional and widely used post-treatment method is to chemically treat polyamide composite membranes with chlorine-containing oxidants. For example, US Patent 4277344A discloses a method for improving water flux by post-treating interfacially polymerized polyamide membranes with sodium hypochlorite solution. However, hypochlorite causes severe chemical degradation of polyamide chains. According to the paper "Degradation of polyamide nanofiltration and reverse osmosis membranes by hypochlorite" published by Do, VT et al. in the academic journal *Environmental Science and Technology*, Vol. 46, No. 2, pp. 852-859, 2012, the chlorination process disrupts the hydrogen bond network between polyamide chains and induces amide bond cleavage and hydrolysis to generate carboxyl-COOH groups, which leads to excessive expansion of the membrane pore size. While this destructive pore expansion significantly increases water flux, it irreversibly reduces the membrane's desalination rate.

[0004] Another common post-processing method is high-temperature thermosetting. For example, Chinese invention patent CN114570218A points out that after preparing polyamide membranes through traditional interfacial polymerization, heat treatment in a high-temperature oven at 100~140℃ is usually required to promote crosslinking. However, this simple high-temperature heat treatment has significant drawbacks. The high-temperature environment accelerates the disordered diffusion of residual monomers in the aqueous and organic phases, which can easily lead to local over-crosslinking of the polyamide separation layer or the generation of physical microcracks. These thermally induced defects not only lead to a decrease in rejection rate but also fail to impart the required hydrophilic antifouling properties to the membrane surface, causing the membrane flux to decay rapidly during actual high-pressure continuous operation.

[0005] To avoid defects caused by high-temperature curing, some existing technologies employ mild acids or polyols to swell polyamide membranes, aiming to increase free volume by weakening interchain forces. However, physical swelling relying solely on reagents such as citric acid or glycerol lacks a targeted repair mechanism. This treatment loosens the polyamide network, exposing a large number of previously physically shielded deep carboxyl groups (-COOH) and residual amino groups (-NH2), resulting in enlarged pores lacking precise size sieving selectivity. Without effective surface repair crosslinking methods, the simply swollen separation membrane also faces severe solute leakage problems. Furthermore, existing technologies have reported the use of tannic acid and amino polymers to construct hydrophilic networks. For example, scholars Qin Li et al. disclosed a method for constructing a hydrophilic crosslinked layer using tannic acid and polyethyleneimine in their paper "Tannic acid-polyethyleneimine crosslinked loose nanofiltration membrane fordye / salt mixture separation," published in the Journal of Membrane Science, Volume 584, 2019. Similarly, while existing technologies have reported the use of tannic acid and single-amino-terminated polyethers to construct hydrophilic networks, when directly applied to the surface of a nascent membrane that has not yet swollen and demasked, the macromolecular modifier lacks strong anchoring points. This simple physical adsorption layer is easily peeled off under high-pressure cross-flow filtration conditions of 1.5–2.0 MPa, failing to maintain long-term stability. Therefore, there is an urgent need to develop a post-treatment method that combines gentle porosification with targeted and robust repair. Summary of the Invention

[0006] To address the technical problem that existing post-treatment methods for polyamide separation composite membranes cannot simultaneously achieve high water flux, high retention rate, and easy coating peeling leading to decreased anti-fouling performance, this invention provides a post-treatment method for polyamide separation composite membranes and the polyamide separation composite membrane prepared therefrom.

[0007] To solve the above-mentioned technical problems, the specific technical solution adopted by the present invention is as follows: On one hand, the present invention provides a post-processing method for polyamide separation composite membranes, comprising the following steps: Step S1: Immerse the nascent polyamide composite membrane in a first post-treatment solution containing citric acid, glycerol, and deionized water for swelling treatment; Step S2: Remove excess residual first post-treatment liquid from the surface of the composite membrane after step S1 using a physical dehydration method; Step S3: The composite membrane after step S2 is immersed in a second post-treatment solution containing tannic acid, mono-terminated amino polyether, antioxidant and deionized water for modification treatment; Step S4: Take out the composite membrane that has been treated in step S3, wash it with water, and dry it to form a shape.

[0008] As a preferred embodiment of the present invention, in the first post-treatment liquid, based on a total mass of 100wt%, the mass fraction of citric acid is 1wt%~3wt%, the mass fraction of glycerol is 5wt%~10wt%, and the remainder is deionized water.

[0009] As a preferred technical solution of the present invention, in step S1, the temperature of the swelling treatment is 50℃~70℃ and the treatment time is 5min~15min.

[0010] As a preferred technical solution of the present invention, in step S2, the physical liquid removal method is air knife blowing liquid removal or rubber pressure roller pressing liquid removal.

[0011] As a preferred embodiment of the present invention, in the second post-treatment liquid, based on a total mass of 100wt%, the mass fraction of tannic acid is 0.2wt%~0.5wt%, the mass fraction of mono-terminated amino polyether is 0.5wt%~1.0wt%, the mass fraction of antioxidant is 0.05wt%~0.1wt%, and the balance is deionized water.

[0012] As a preferred embodiment of the present invention, in step S3, the pH of the second post-treatment solution is 7.0~7.5, and the second post-treatment solution is prepared and used immediately or used within 2 hours after preparation; the antioxidant is ascorbic acid.

[0013] As a preferred embodiment of the present invention, the number-average molecular weight of the single-terminated amino polyether is 600-1000.

[0014] As a preferred technical solution of the present invention, in step S3, the temperature of the modification treatment is 20℃~30℃ and the treatment time is 10min~20min; in step S4, the drying conditions are drying in air at a temperature of 40℃~50℃.

[0015] As a preferred embodiment of the present invention, the nascent polyamide composite membrane is prepared by interfacial polymerization of an aqueous solution containing m-phenylenediamine and an organic solution containing trimesoyl chloride on a porous support base membrane; the porous support base membrane is a polysulfone porous support membrane or a polyethersulfone porous support membrane.

[0016] On the other hand, the present invention also provides a polyamide separation composite membrane prepared by the above-described post-processing method for polyamide separation composite membrane.

[0017] The mechanism of the synergistic effect of this invention is explained as follows: This invention constructs a synergistic mechanism of mild pore induction and targeted repair through a two-step post-treatment solution. In step S1, citric acid in the first post-treatment solution not only effectively washes away unreacted free monomers, but its mild acidity also weakens the hydrogen bond network between polyamide segments, inducing conformational relaxation and microscopic swelling of the polyamide separation layer. This unmasking process exposes a large amount of carboxyl-COOH and residual amino-NH2 groups, which were originally physically shielded by the highly cross-linked network, to the membrane surface and pore walls. At the same time, glycerol, with its polyol properties, penetrates deep into the pores to provide physical support and pore retention. The physical dehydration in step S2 effectively prevents the acidic residual liquid from interfering with the pH of subsequent processes, ensuring the chemical stability of the modified solution. In step S3, the added antioxidant ascorbic acid inhibits the oxidative self-polymerization of tannic acid by preferentially consuming dissolved oxygen in the solution. Under this neutral and mild environmental protection, tannic acid and mono-terminated amino polyethers do not undergo violent self-polymerization precipitation in the solution, but instead form stable soluble hydrogen-bonded complexes. When the supramolecular complex comes into contact with the demasking-treated membrane surface, the abundant carboxyl-COOH and residual amino-NH2 groups exposed on the membrane surface form an extremely dense multi-hydrogen bond anchoring network with these exposed groups. Simultaneously, the single-terminated amino polyether exhibits strong electrostatic attraction and in-situ assembly with the polyamide matrix. The first-stage swelling and demasking provides numerous targeted anchoring points for the second-stage complex modification, preventing it from being eroded off by high-pressure erosion. Conversely, the second-stage supramolecular complex provides sealing repair and hydrophilic modification for the micropores opened up in the first stage. Both are indispensable, jointly constructing an extremely robust hydrophilic antifouling layer.

[0018] Compared with the prior art, the present invention has the following beneficial effects: Firstly, this invention breaks through the traditional trade-off between water flux and desalination rate. By using citric acid for gentle pore expansion in the early stage combined with targeted and precise repair of macroporous defects by complexing in the later stage, the prepared composite membrane achieves a multiple increase in pure water flux while maintaining or even slightly improving the original high rejection rate, effectively improving membrane separation efficiency.

[0019] Secondly, the composite membrane prepared by this invention exhibits excellent long-term stability and antifouling performance. Thanks to the strong hydrogen bonds and electrostatic synergistic anchoring effect between the surface unmasking sites and the tannic acid complex, the modified layer is not easily detached or peeled off under long-term high-pressure water flow. Simultaneously, the introduction of single-terminated amino polyethers constructs a highly hydrated antifouling barrier on the membrane surface, significantly reducing the adsorption and adhesion of organic pollutants such as proteins, resulting in a high flux recovery rate after continuous operation.

[0020] Third, the post-treatment reagents used in this invention are all environmentally friendly and low-cost, and the reaction conditions are mild, avoiding the physical defects caused by traditional high-temperature curing and the chemical degradation caused by strong oxidant chlorination. By introducing liquid removal and oxygen-consuming antioxidant processes, the solution system is stable and controllable, with good operational repeatability, and has extremely high feasibility for industrial scale-up. Attached Figure Description

[0021] Figure 1 This is a scatter plot comparing the game effect of water flux and desalination rate of the polyamide separation composite membranes prepared in Examples 1-3 and Comparative Examples 1-4 of the present invention.

[0022] Figure 2 This is a line graph showing the desalination rate of the polyamide separation composite membranes prepared in Example 1 and Comparative Example 3 of the present invention as a function of time in a continuous high-pressure cross-flow filtration test.

[0023] Figure 3 The graph shows the normalized pure water flux versus time curves of the polyamide separation composite membranes prepared in Example 1 and Comparative Example 1 of this invention during dynamic testing of resistance to organic pollution. Detailed Implementation

[0024] To make the objectives, technical solutions, and beneficial effects of this invention clearer, the invention will be further described below with reference to specific embodiments. It should be noted that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of this invention.

[0025] Example 1

[0026] This embodiment provides a post-processing method for polyamide separation composite membranes, the specific steps of which are as follows: Step S1: A nascent polyamide composite membrane was prepared by interfacial polymerization of a 2.0 wt% m-phenylenediamine aqueous solution and a 0.15 wt% trimesoyl chloride n-hexane solution on a polysulfone porous support membrane. The nascent polyamide composite membrane was then immersed in a first post-treatment solution at 60°C for 10 min to induce swelling. The first post-treatment solution contained 2.0 wt% citric acid, 8.0 wt% glycerol, and the remainder was deionized water.

[0027] Step S2: Remove the composite membrane and use an air knife to remove excess residual first post-treatment solution from the surface of the composite membrane.

[0028] Step S3: Immerse the dehydrated composite membrane in a second post-treatment solution at 25°C for 15 minutes for modification. The second post-treatment solution contains 0.3 wt% tannic acid, 0.8 wt% single-terminated amino polyether (Jeffamine, M-1000) with a number average molecular weight of 1000, 0.08 wt% ascorbic acid, and the remainder is deionized water. This second post-treatment solution is freshly prepared and the pH is adjusted to 7.2 using dilute NaOH solution.

[0029] Step S4: Take out the modified composite membrane, rinse it with deionized water, and gently dry it in air at 45°C to shape it.

[0030] Example 2

[0031] This embodiment provides a post-processing method for polyamide separation composite membranes. The specific steps are basically the same as those in Embodiment 1, except that extreme process conditions are used to verify the stability of the process.

[0032] In step S1, the swelling treatment temperature is 70℃ and the treatment time is 15 min. The mass fraction of citric acid in the first post-treatment solution is 3.0 wt%, and the mass fraction of glycerol is 10.0 wt%.

[0033] In step S3, the modification treatment temperature is 30℃ and the treatment time is 20 min. The second post-treatment solution contains 0.5 wt% tannic acid, 1.0 wt% single-terminated amino polyether (Jeffamine, M-1000) with a number average molecular weight of 1000, and 0.1 wt% ascorbic acid. The pH is adjusted to 7.5 using dilute NaOH solution.

[0034] Example 3

[0035] This embodiment provides a post-processing method for polyamide separation composite membranes. The specific steps are basically the same as those in Embodiment 1, except that lower limit process conditions are used.

[0036] In step S1, the swelling treatment temperature is 50℃ and the treatment time is 5 min. The mass fraction of citric acid in the first post-treatment solution is 1.0 wt%, and the mass fraction of glycerol is 5.0 wt%.

[0037] In step S3, the modification treatment temperature is 20℃ and the treatment time is 10 min. The second post-treatment solution contains 0.2 wt% tannic acid, 0.5 wt% single-terminated amino polyether (Jeffamine, M-600) with a number average molecular weight of 600, and 0.05 wt% ascorbic acid. The pH is adjusted to 7.0 using dilute NaOH solution.

[0038] Comparative Example 1 This comparative example provides a conventional nascent membrane. The difference from Example 1 is that after the nascent polyamide composite membrane is prepared, it is not treated with the first and second post-treatment solutions, but is directly washed with room temperature pure water and dried at 45°C.

[0039] Comparative Example 2 This comparative example provides a membrane that undergoes only mild pore-forming treatment. The difference from Example 1 is that step S3 is omitted, and the nascent polyamide composite membrane is directly washed and dried after being treated with the first post-treatment solution and dehydrated with an air knife.

[0040] Comparative Example 3 This comparative example provides a membrane that undergoes only surface modification treatment. The difference from Example 1 is that step S1 is omitted, and the nascent polyamide composite membrane is directly immersed in the second post-treatment solution after being purged with an air knife.

[0041] Comparative Example 4 This comparative example provides a membrane for verifying the effects of extreme acid degradation. The difference from Example 2 is that glycerol is not added to the first post-treatment solution, and the repair and modification process in step S3 is omitted.

[0042] Performance testing methods The composite membranes prepared in Examples 1-3 and Comparative Examples 1-4 were cut to appropriate sizes and placed into a cross-flow filtration evaluation device, with an effective membrane area of ​​42 cm².

[0043] (1) Basic separation performance test: Using a NaCl aqueous solution with a concentration of 2000ppm as the feed liquid, the system was pre-pressurized for 30min at an operating pressure of 1.5MPa and a temperature of 25℃, and then operated stably. The permeate was collected, and the pure water flux and NaCl desalination rate were calculated.

[0044] (2) Long-term high-pressure cross-flow stability test: Under the same test conditions as above, the device was kept running continuously for 100 hours. The desalination rate at different operating time points was recorded to evaluate the anchoring stability of the modified layer.

[0045] (3) Dynamic performance test against organic fouling: The initial water flux was tested with pure water and stabilized for 120 min; then the feed solution was switched to a 1000 ppm bovine serum albumin solution and continuously filtered for 840 min to induce membrane fouling; then the membrane was shut down and the membrane surface was rinsed with pure water without pressure for 30 min (840~870 min); after rinsing, the pressure was increased again and the pure water test was carried out for 990 min. The flux recovery rate before and after cleaning was calculated.

[0046] Characterization results and analysis Table 1. Comparison of core post-processing parameters and initial separation performance of each embodiment and comparative example.

[0047] Table 2. Long-term crossflow stability and anti-fouling dynamic test data for each embodiment and comparative example.

[0048] First, looking at the specific values ​​in Table 1, Comparative Example 1 (untreated blank membrane) exhibits low flux characteristics; while Comparative Example 2 (pore expansion only) shows a significant increase in flux, its initial desalination rate drops drastically to 91.2% (salt leakage occurs). However, Examples 13 of the present invention achieve a double improvement. Taking Example 1 as an example, while its initial desalination rate increases from 98.5% in Comparative Example 1 to 99.6%, the initial pure water flux jumps dramatically to 64.7 L / m²·h, an increase of 84.3%. This numerically demonstrates that the first step of pore expansion combined with the second step of targeted repair not only did not cause salt leakage, but also further improved the membrane's compactness because the supramolecular complex perfectly filled the macropore defects. Furthermore, observation... Figure 1 The scatter distribution reveals that the data points in Comparative Example 1 and Comparative Example 2 directly reflect the inverse correlation between flux and desalination rate, while the data points in Example 13 completely deviate from this conventional trajectory, hanging high above... Figure 1 The upper right region. The independence of this spatial distribution visually strongly demonstrates that the invention achieves a substantial leap in performance.

[0049] Secondly, as shown in the test data in Table 2, Comparative Example 3 (modification only, no pore enlargement) lacked the carboxyl and amino sites exposed in the first step of pore demasking, so its coating only remained on the membrane surface, and the desalination rate dropped to 95.0% after 100 hours. Comparative Example 2 (pore enlargement only, no modification) inevitably experienced a drop in pure water flux to 81.5 L / m²·h after 100 hours of operation due to the high-pressure compaction effect, and because of the lack of coating protection, the internal pores deformed under scouring, further reducing the desalination rate to 88.4%. Conversely, in Example 1, the pure water flux only experienced a slight decrease due to compaction after 100 hours, and the desalination rate remained as high as 99.5%. Furthermore, Figure 2 The continuous operation line graph also visually confirms this conclusion: the desalination rate curve of Comparative Example 3 shows a clear and continuous downward trend, indicating the continuous peeling of the unanchored coating; while the desalination rate curve of Example 1 is like a perfect horizontal straight line throughout the entire 100h cycle. This macroscopic evidence demonstrates that the tannic acid complex and the unmasking sites form an extremely robust targeted anchoring network, achieving long-term non-detachment of the coating.

[0050] Furthermore, the detailed dynamic fouling data in Table 2 show that after the introduction of bovine serum albumin (BSA) to induce fouling, Example 1, after shutdown and pure water rinsing, saw its flux rapidly recover to 62.6 L / m²·h, with a flux recovery rate as high as 96.8%. In contrast, Comparative Example 1's flux only recovered to 26.3 L / m²·h after rinsing, with a recovery rate of only 74.9%. This numerical comparison indicates that the examples constructed a dense, highly hydrated antifouling barrier on the membrane surface, effectively inhibiting the irreversible adsorption of pollutants. Meanwhile, Figure 3 The dynamic curve vividly presents the elution response characteristics of the antifouling barrier: during the pure water rinsing stage of shutdown (i.e., Figure 3 After the physical disconnection of the curve in Example 1, the curve showed a significant step rebound, rapidly approaching the height of the initial test stage; while the curve segment of Comparative Example 1 after cleaning remained at the bottom of the chart. The huge visual difference before and after cleaning intuitively demonstrates that the modified network of this invention can greatly reduce the irreversibility of organic pollution.

[0051] Finally, by comparing the data in Tables 1 and 2, it can be seen that even with the extreme upper limit pore-forming conditions of 3.0 wt% citric acid and 70°C, Example 2 maintained high desalination rates of 99.1% and 99.0% at the initial and 100-hour levels, respectively. In contrast, Comparative Example 4, which involved the removal of the glycerol pore-retaining agent and the repair step, suffered from both mechanical compaction and severe chemical degradation. After 100 hours, its flux dropped to 86.4 L / m²·h, and its desalination rate plummeted to only 80.6%. This thoroughly confirms that under the protection of the special mild pore-retaining formulation of this invention, severe chemical degradation leading to polyamide chain segment breakage will not occur, and the process window is wide and safe.

[0052] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A post-processing method for a polyamide separation composite membrane, characterized in that, Includes the following steps: Step S1: Immerse the nascent polyamide composite membrane in a first post-treatment solution containing citric acid, glycerol, and deionized water for swelling treatment; Step S2: Remove excess residual first post-treatment liquid from the surface of the composite membrane after step S1 using a physical dehydration method; Step S3: The composite membrane after step S2 is immersed in a second post-treatment solution containing tannic acid, mono-terminated amino polyether, antioxidant and deionized water for modification treatment; Step S4: Take out the composite membrane that has been treated in step S3, wash it with water, and dry it to form a shape.

2. The post-processing method for the polyamide separation composite membrane according to claim 1, characterized in that, In the first post-treatment solution, based on a total mass of 100wt%, the mass fraction of citric acid is 1wt%~3wt%, the mass fraction of glycerol is 5wt%~10wt%, and the remainder is deionized water.

3. The post-processing method for the polyamide separation composite membrane according to 1 or 2, characterized in that, In step S1, the swelling treatment temperature is 50℃~70℃, and the treatment time is 5min~15min.

4. The post-processing method for the polyamide separation composite membrane according to claim 1, characterized in that, In step S2, the physical liquid removal method is either air knife blowing or rubber roller pressing to remove liquid.

5. The post-processing method for the polyamide separation composite membrane according to claim 1, characterized in that, In the second post-treatment solution, based on a total mass of 100wt%, the mass fraction of tannic acid is 0.2wt%~0.5wt%, the mass fraction of mono-terminated amino polyether is 0.5wt%~1.0wt%, the mass fraction of antioxidant is 0.05wt%~0.1wt%, and the balance is deionized water.

6. The post-processing method for the polyamide separation composite membrane according to 1 or 5, characterized in that, In step S3, the pH of the second post-treatment solution is 7.0~7.5, and the second post-treatment solution is prepared and used immediately or used within 2 hours after preparation; the antioxidant is ascorbic acid.

7. The post-processing method for the polyamide separation composite membrane according to 1 or 5, characterized in that, The number-average molecular weight of the single-terminated amino polyether is 600-1000.

8. The post-processing method for the polyamide separation composite membrane according to claim 1, characterized in that, In step S3, the temperature of the modification treatment is 20℃~30℃, and the treatment time is 10min~20min; in step S4, the drying conditions are drying in air at a temperature of 40℃~50℃.

9. The post-processing method for the polyamide separation composite membrane according to claim 1, characterized in that, The nascent polyamide composite membrane is prepared by interfacial polymerization of an aqueous solution containing m-phenylenediamine and an organic solution containing trimesoyl chloride on a porous support base membrane; the porous support base membrane is a polysulfone porous support membrane or a polyethersulfone porous support membrane.

10. A polyamide separation composite membrane prepared by any of the post-processing methods described in 1 to 9.

Citation Information

Patent Citations

  • Polyamide composite membrane and preparation process thereof

    CN114570218A

  • Interfacially synthesized reverse osmosis membrane

    US4277344A